Optimasi Pemahaman Kader Posyandu terhadap Konsep 'Ibu Bahagia, Keluarga Bahagia' di Kota Malang - Hidayati, Laely; Royani Meisani, Diah; Agnuristyaningrum, Alfi; Salwa Nurwachidah, Nanda; Arumiyati Anwar, Seila (Journal of Issues in Midwifery, 2024)
Posyandu plays a central role in organizing primary healthcare services in Indonesia. Posyandu cadres, as the primary agents providing education to mothers, aim to create healthy and happy families. Family happiness is not only related to physical health but also involves psychological and social dimensions. This activity was conducted to enhance the capacity and understanding of the concept of "happy mother" in the context of a happy family among 49 Posyandu cadres in Malang City. The training approach adopted includes lectures, group discussions, and assessments to measure changes in the understanding of Posyandu cadres. The results of pre and post-tests indicate a significant improvement in the understanding of Posyandu cadres regarding the concepts of a happy mother and a happy family, increasing from a score of 54.5 to 79. With a deeper understanding, Posyandu cadres are expected to provide more comprehensive support. The increased capacity of Posyandu cadres also provides opportunities for them to design and implement more effective educational programs on the concepts of a happy mother and a happy family. Therefore, it is anticipated that these efforts will bring about a significantly positive impact on the overall well-being of families and the community. Keywords: Happy Family, Happy Mother, Posyandu Cadres